Tolong kak please

Posted on

Jawaban:

6a² + 8ab

= 2a × (3a + 4b)

.

Pembuktian :

2a (3a + 4b)

= (2a × 3a) + (2a × 4b)

= (2 × 3)a² + (2 × 4)ab

= 6a² + 8ab

#Cmiiw

- oxed{ f{Answer : by : oxed{ f{ 
ed{sandsay}}}}} -

Leave a Reply

Your email address will not be published. Required fields are marked *

Tolong kak please

Posted on

Jawaban:

6a² + 8ab

= 2a × (3a + 4b)

.

Pembuktian :

2a (3a + 4b)

= (2a × 3a) + (2a × 4b)

= (2 × 3)a² + (2 × 4)ab

= 6a² + 8ab

#Cmiiw

- oxed{ f{Answer : by : oxed{ f{ 
ed{sandsay}}}}} -

Leave a Reply

Your email address will not be published. Required fields are marked *

Leave a Reply

Your email address will not be published. Required fields are marked *

Leave a Reply

Your email address will not be published. Required fields are marked *

Leave a Reply

Your email address will not be published. Required fields are marked *

Leave a Reply

Your email address will not be published. Required fields are marked *